2021
DOI: 10.3389/fmicb.2021.765310
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Patterns and Ecological Preferences of the Photobionts Associated With the Lichen-Forming Genus Parmelia

Abstract: The worldwide, ecologically relevant lichen-forming genus Parmelia currently includes 41 accepted species, of which the Parmelia sulcata group (PSULgp) and the Parmelia saxatilis group (PSAXgp) have received considerable attention over recent decades; however, phycobiont diversity is poorly known in Parmelia s. lat. Here, we studied the diversity of Trebouxia microalgae associated with 159 thalli collected from 30 locations, including nine Parmelia spp.: P. barrenoae, P. encryptata, P. ernstiae, P. mayi, P. om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 93 publications
(140 reference statements)
3
7
1
Order By: Relevance
“…This evidence suggests that the two lichens are highly selective (sensu Beck et al 2002) for this phycobiont taxon across a large geographical range in the Northern Hemisphere that includes various bioclimatic and biogeographical areas. These results agree with other observations in which identical phycobiont strains associated with a single mycobiont in distant geographical areas (Fernández-Mendoza et al 2011;Garrido-Benavent et al 2020;Moya et al 2021). The fact that P. borreri and P. subrudecta usually reproduce by soredia might explain why these lichens retain the same microalgal species as their photosynthetic partner; however, genetic differentiation may still be occurring, for example, owing to intrathalline somatic mutations occurring during algal cell division (Dal Grande et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This evidence suggests that the two lichens are highly selective (sensu Beck et al 2002) for this phycobiont taxon across a large geographical range in the Northern Hemisphere that includes various bioclimatic and biogeographical areas. These results agree with other observations in which identical phycobiont strains associated with a single mycobiont in distant geographical areas (Fernández-Mendoza et al 2011;Garrido-Benavent et al 2020;Moya et al 2021). The fact that P. borreri and P. subrudecta usually reproduce by soredia might explain why these lichens retain the same microalgal species as their photosynthetic partner; however, genetic differentiation may still be occurring, for example, owing to intrathalline somatic mutations occurring during algal cell division (Dal Grande et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Parmelia saxatilis (L.) Ach. and P. sulcata Taylor species complexes; Moya et al 2021), or in phylogeographical assessments based on large specimen sampling. For example, diverse Trebouxia species and infraspecific lineages were found in association with Cetraria aculeata (Schreb.)…”
Section: Introductionmentioning
confidence: 99%
“…The new species Trebouxia lynnae belongs to Trebouxia clade A (as shown here and in previous studies [ 5 , 6 , 9 , 10 , 31 , 86 ]) and was found to be a sister species of T. jamesii ( Figure 4 ). BI and ML analyses were topologically congruent and high posterior probabilities (PP) and bootstrap supports (BS) were obtained for all species-level lineages.…”
Section: Resultssupporting
confidence: 84%
“…the advancement of the lichen thallus over miniaturized and large-scale biological scales was clearly affected by the nearness of the two primary symbionts within the environment and by the portion of selectivity and specificity that either symbiont appears for each other (Moya et al 2021). Typically, commonly considered a versatile procedure of the mycobiont to colonize a more extensive extent of natural conditions, selecting the leading adjusted phycobiont (Muggia et al 2013).…”
Section: Victory Withinmentioning
confidence: 99%
“…The density of lichens is reassessed based on the morpho chemotic features and its updated taxonomic keys. The impact of the susceptibility of lichen species to abiotic and biotic changes was influenced by the ability of the thallus accumulation within challenging environments through physiological adhesiveness (Kodnik et al 2015;Moya et al 2021). Most corticolous and saxicolous taxa were reported with multiple species rich in nature (Belguidoum et al 2022a,b).…”
Section: Victory Withinmentioning
confidence: 99%